2013
DOI: 10.1186/1471-2121-14-33
|View full text |Cite
|
Sign up to set email alerts
|

ERK-associated changes in E2F4 phosphorylation, localization and transcriptional activity during mitogenic stimulation in human intestinal epithelial crypt cells

Abstract: BackgroundThe transcription factor E2F4 controls proliferation of normal and cancerous intestinal epithelial cells. E2F4 localization in normal human intestinal epithelial cells (HIEC) is cell cycle-dependent, being cytoplasmic in quiescent differentiated cells but nuclear in proliferative cells. However, the intracellular signaling mechanisms regulating such E2F4 localization remain unknown.ResultsTreatment of quiescent HIEC with serum induced ERK1/2 activation, E2F4 phosphorylation, E2F4 nuclear translocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
2
15
0
1
Order By: Relevance
“…Our results support this hypothesis since the mutation of the conserved Thr249/T251 motif of mouse E2F4, which is susceptible to be phosphorylated (21), is crucial for maintaining neuronal quiescence and brain homeostasis in the presence of elevated levels of A. This is consistent with our previous observation that E2F4 is associated with phosphoThr immunoreactivity in cortical neurons from APP/PS1 mice (27), and that E2F4 phosphorylation can lead to cell cycle progression (25,75). In stressed neurons, E2F4 phosphorylation could favor the expression of mitotic regulators (25,74), and cell cycleindependent genes involved in the etiology of AD, thus explaining the capacity of E2F4DN to restore normal E2F4 function and prevent several AD-associated processes.…”
Section: Discussionsupporting
confidence: 92%
“…Our results support this hypothesis since the mutation of the conserved Thr249/T251 motif of mouse E2F4, which is susceptible to be phosphorylated (21), is crucial for maintaining neuronal quiescence and brain homeostasis in the presence of elevated levels of A. This is consistent with our previous observation that E2F4 is associated with phosphoThr immunoreactivity in cortical neurons from APP/PS1 mice (27), and that E2F4 phosphorylation can lead to cell cycle progression (25,75). In stressed neurons, E2F4 phosphorylation could favor the expression of mitotic regulators (25,74), and cell cycleindependent genes involved in the etiology of AD, thus explaining the capacity of E2F4DN to restore normal E2F4 function and prevent several AD-associated processes.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, ERK1/2-mediated phosphorylation of E2F4 on serines S244 and S384 promotes its nuclear localization in proliferating intestinal cells 38 . Phosphorylation of E2F4 on threonines T261 and T263 by p38 MAPK allows it to bind and activate cell cycle genes during cell cycle re-entry of neurons (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of E2F4 , there are no significant changes in mRNA expression but our analysis shows it exhibits significantly increased regulatory activity. This suggests that the regulatory activity of E2F4 cannot be reflected by mRNA level presumably due to post-transcriptional and post-translational regulation (36, 37). In fact, it has been shown that E2F phosphorylation and localization can be regulated by MEK/ERK activation, leading to changes in its transcriptional activity (36).…”
Section: Discussionmentioning
confidence: 99%